THE ROLE OF COLLOCATIONS IN LANGUAGE LEARNING AND LINGUISTIC ANALYSIS - Mahmudova Sarvinoz (ZAMONAVIY TA’LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2025)
Annotation: This article investigates the role of collocations in language learning and linguistic research. Collocations, defined as habitual co-occurrences of words, are essential for producing natural, fluent, and idiomatic language. Drawing on corpus-based studies and pedagogical research, the article analyzes the types of collocations, their significance for vocabulary acquisition, reading comprehension, speaking, and writing, and their implications for ESL/EFL teaching. It emphasizes effective instructional strategies, including corpus analysis, collocation dictionaries, and task-based exercises, while addressing common challenges and misconceptions. The study concludes that understanding and using collocations enhances learners’ communicative competence and provides valuable insights for both practical language teaching and theoretical linguistic analysis.